ChemInform Abstract: A Lightweight Shape‐Memory Magnesium Alloy. Issue 41 (September 2016) - Ogawa, Yukiko; Ando, Daisuke; Sutou, Yuji; Koike, Junichi
Abstract: A β‐type Mg—20.5 at% Sc alloy exhibits superelasticity of 4.4% at ‐150 °C and shape recovery upon heating.